ENHANCE-D: protocol for a pragmatic, 3-arm, randomised controlled trial comparing the impact of enhanced smoking cessation interventions to very brief advice for adult smokers in dental care settings - Richard Holliday; Nina Wilson; Vicky Ryan; Chrissie Butcher; Tara Homer; Philippa Watts; Dorcas Kareithi; Paul Blaylock; Laura Ternent; Roland Finch; Susan M. Bissett; Adam Todd; et al. (Trials)
Abstract Background Smoking is a key contributor to health inequalities, particularly impacting oral health. Periodontal (gum) health is significantly affected by smoking. With their extensive reach, regular and frequent patient contact, and potential teachable moments, dental teams are well placed to support patients to stop smoking. This is currently mainly provided through Very Brief Advice (VBA) interventions and so there is scope to enhance the cessation support offered. A large definitive trial is needed to confirm whether this would lead to improved smoking quit rates, improved oral health, and be good value for money. Methods The ENHANCE-D trial is a multi-centre, pragmatic, definitive, 3-arm, parallel group, individually randomised controlled superiority trial, including an internal pilot, conducted in NHS dental settings. In total, 1215 patients who are current regular smokers will be randomly allocated using a 1:2:2 ratio to the following: (i) VBA; (ii) the offer of a standard course of Nicotine Replacement Therapy (NRT); (iii) or the offer of an e-cigarette starter kit. A subgroup of patients with periodontitis (gum disease) will have additional oral examinations and samples collected. The primary outcome is biochemically verified smoking abstinence at 6 months. A key secondary outcome is the percentage of periodontal sites with probing pocket depths (PPDs) ≥ 5 mm at 6 months in the periodontitis subgroup. Participants will be blinded to the purpose of the trial and not be aware of the treatment packages. Periodontal health outcomes will be recorded by trained and aligned assessors, blinded to intervention arm. Participant recruitment started in July 2022 with an internal pilot progressing to the main trial in May 2023. A qualitative process evaluation will explore participants’ experiences of receiving the study interventions, alongside the views of dental teams, NHS commissioners, service managers, and policymakers. An economic evaluation will include a cost-effectiveness analysis and a cost–benefit analysis. Discussion This will be the largest contemporary randomised trial of smoking cessation interventions in dental settings and one of the first to evaluate enhanced interventions. E-cigarettes were included as an intervention due to growing evidence of their effectiveness. They will be compared to VBA and NRT, and oral health outcomes assessed. The multi-centre, pragmatic design of this trial supports the external validity and potential for impacting clinical practice. Trial registration ISRCTN 13158982. Registered on 10 May 2022. https://www.isrctn.com/ISRCTNISRCTN13158982